The Effect Prediction of Planting Area Expansion Policy on Rice Production - Sulaiman, Andi Amran; Setiyanto, Adi; Basit, Abdul; Sinuraya, Julia Forcina; Hermawan, Hari; Nida, Fajri Shoutun; Astari, Annisa Fauzia; Mardianto, Sudi; Bahrun, Abd Haris; Arsyad, Muhammad; Raisa, Daeva Mubarika (AGRIVITA Journal of Agricultural Science, 2026)
Ministry of Agriculture has established the Planting Area Expansion (called PAT) Program to increase rice production by expanding the harvest area. The study used a time-series analysis approach with the structured vector autoregressive (SVAR) method with monthly data for the period January 1993-March 2025. The results of the analysis show that rice production in 2025 is estimated to reach 58.43 million tons of milled dry grain, an increase of 5.29 million tons (9.95%) compared to production in 2024, as a contribution of the program to expand the planting area and land optimalization (known as OPLAH), irrigation development, pump and pipeline installation, new rice field cultivation of 1.62 million tons or 30.56 percent, worth IDR 12.58 trillion. Three main recommendations are as follows: (1) the performance of water pump and OPLAH assistance in 2024 should be ensured to proceed in 2025, and OPLAH as well as new rice field development in 2025 should be ensured to be fully realized, with some of the new rice fields already able to be planted with rice; (2) controlling the rate of rice field conversion to maintain the availability of rice cultivation land; and (3) optimizing farmer assistance by field agricultural extension workers.